An Overview of Menstrual Hygiene Management in Female Adolescent - Fayakun Nur Rohmah; Iyan Safitri (Universitas 'Aisyiyah Yogyakarta, 2021)
Lack of knowledge about menstrual hygiene management and poor water sanitation are the main problems for female adolescents. This study aims to determine the description of menstrual hygiene management's implementation in boarding school's students in Bantul, Yogyakarta. This research is a descriptive study with a cross-sectional approach. The sampling technique in this study was a total population with 38 students as the samples. The collecting data process was done using questionnaires. The result show that female adolescents' behaviour regarding personal hygiene during menstruation falls into the excellent category (81.6%) and majority students got knowledge about menstrual hygiene management from their parents (47.4%).